Genomics and Breeding for Climate-Resilient Crops Vol. 2 Target Traits - Kole, Chittaranjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Climate change is expected to have a drastic impact on agronomic conditions including temperature, precipitation, soil nutrients, and the incidence of disease pests, to name a few. To face this looming threat, significant progress in developing new breeding strategies has been made over the last few decades. The second volume of Genomics and Breeding for Climate-Resilient Crops describes various genomic and breeding approaches for the genetic improvement of the major target traits. Topics covered include: flowering time; root traits; cold, heat and drought tolerance; water use efficiency; flooding and submergence tolerance; disease and insect resistance; nutrient use efficiency; nitrogen fixation; carbon sequestration; and greenhouse gas emissions.
Flowering time -- Root Characters -- Cold Tolerance -- Breeding for Heat Tolerance in Annual Crops -- Drought -- Water Use Efficiency: Governed By an Interactive Network of Physical, Biochemical and Hydraulic Processes -- Flooding and Submergence Tolerance in Rice -- Application of Genomics to Breed Disease Resistant Crop Varieties -- Insect Resistance -- Nutrient Use Efficiency -- Nitrogen Fixation and Assimilation -- Carbon Sequestration -- Plant Breeding Approaches to Reducing Greenhouse Gas Emissions.
Keywords: Life sciences; Agriculture; Plant breeding; Life Sciences; Plant Breeding/Biotechnology.; Climate Change Impacts; Agriculture; Plant Genetics & Genomics